1999
DOI: 10.1002/(sici)1096-8628(19990521)84:2<151::aid-ajmg12>3.0.co;2-t
|View full text |Cite
|
Sign up to set email alerts
|

Genetic polymorphisms in methylenetetrahydrofolate reductase and methionine synthase, folate levels in red blood cells, and risk of neural tube defects

Abstract: Folic acid administration to women in the periconceptional period reduces the occurrence of neural tube defects (NTDs) in their offspring. A polymorphism in the gene encoding methylenetetrahydrofolate reductase (MTHFR), 677C-->T, is the first genetic risk factor for NTDs in man identified at the molecular level. The gene encoding another folate-dependent enzyme, methionine synthase (MTR), has recently been cloned and a common variant, 2756A-->G, has been identified. We assessed genotypes and folate status in 5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

7
120
2
2

Year Published

1999
1999
2012
2012

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 254 publications
(131 citation statements)
references
References 37 publications
7
120
2
2
Order By: Relevance
“…However, the control mothers showed no significant difference in biochemical profile as a function of the MTHFR 677C-T polymorphism, probably because there were no differences in folate or vitamin B 12 intake as a function of the genotype. This finding supports the hypothesis that serum levels of folate and vitamin B 12 can be attributed to both genetic and nutritional factors (10,41) .…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…However, the control mothers showed no significant difference in biochemical profile as a function of the MTHFR 677C-T polymorphism, probably because there were no differences in folate or vitamin B 12 intake as a function of the genotype. This finding supports the hypothesis that serum levels of folate and vitamin B 12 can be attributed to both genetic and nutritional factors (10,41) .…”
Section: Discussionsupporting
confidence: 88%
“…However, studies in other countries reported significantly lower RBC folate concentrations in case mothers than in control mothers (10)(11)(12)(38)(39)(40) .…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Ideally, such studies also should evaluate interactions with environmental factors, such as blood folate levels 50 and multivitamin supplement use. 51 Other gene-environment 52 and genegene interactions 52,53 might also occur.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that one particular MTHFR mutation is present in 16% of mothers, 10% of fathers and 13% of children with spina bifida compared with 5% of controls. 39,40 Individuals with elevated homocysteine levels caused by this mutation are prevalent in the population because these levels pose no serious immediate health threat to the carrier parent. However, further evidence is appearing to show that a carrier woman's pregnancy is at risk and perhaps, her cardiovascular health later in life.…”
Section: Discussionmentioning
confidence: 99%